Use, access and motivation of older people towards information and communication technologies - González Gómez, Rita Vanessa (2023)
The Costa Rican Gerontological Association (AGECO) carried out a National Study during the year 2022 on the use, access, and motivation of the elderly towards Information and Communication Technologies in order to analyze the inclusion needs of the elderly ini spaces of virtual participation and the experience of active ageing. Methodologically, a quantitative study was developed in which 1,100 older people were interviewed nationwide with proportional percentages based on the number of older people living in the 7 provinces of Costa Rica. A margin of error of +0-3% was reached, as well as 95% of confidence in the sample. The results of the study show the needs for inclusion of use, access, and motivation of the elderly, as well as alternatives to respond to these in a comprehensive way and integral form with a gerontological perspective.